Japan's Foreign Policy Making Central Government Reforms, Decision-Making Processes, and Diplomacy - Zakowski, Karol (Springer International Publishing, 2018)
This book evaluates the impact of the 2001 central government reforms on effective foreign policy making in Japan. It puts a special focus on the evolution of the domestic institutional factors and decision-making processes behind Japan's foreign policy, while also analyzing the development of Japan's external relations with various other countries, such as the US, China and North Korea. Adhering to the neoclassical realist approach, the authors show that, thanks to a more independent Kantei-based form of diplomacy, Japan's prime ministers were able to strategically respond to international developments, and to pursue their own diplomatic endeavors more boldly. At the same time, they demonstrate that the effectiveness of this proactive posture was still heavily dependent on the decision-makers' ability to form cohesive coalitions and select suitable institutional tools, which enabled them to influence domestic and international affairs. .